2018
DOI: 10.1242/jeb.175372
|View full text |Cite
|
Sign up to set email alerts
|

Energetic costs of locomotion in bears: is plantigrade locomotion energetically economical?

Abstract: Ursids are the largest mammals to retain a plantigrade posture. This primitive posture has been proposed to result in reduced locomotor speed and economy relative to digitigrade and unguligrade species, particularly at high speeds. Previous energetics research on polar bears () found locomotor costs were more than double predictions for similarly sized quadrupedal mammals, which could be a result of their plantigrade posture or due to adaptations to their Arctic marine existence. To evaluate whether polar bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 68 publications
1
49
1
Order By: Relevance
“…The relationship we developed on the treadmill was limited to a maximum speed of 3 km/hr, which may have limited our ability to predict energy expenditure at greater speeds. However, in polar bears, V̇O 2 has been shown to increase linearly at speeds up to 5.4 km/hr (Pagano, Carnahan et al, ) and free‐ranging polar bears, including those in this study, rarely exceed this speed (Pagano, Carnahan et al, ; Whiteman et al, ). Another factor that can influence the relationship between ODBA and V̇O 2 , and thus cost of locomotion, is uneven surfaces including moving on rough or icy surfaces, and traversing inclines and declines (Halsey, ; Halsey et al, ).…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…The relationship we developed on the treadmill was limited to a maximum speed of 3 km/hr, which may have limited our ability to predict energy expenditure at greater speeds. However, in polar bears, V̇O 2 has been shown to increase linearly at speeds up to 5.4 km/hr (Pagano, Carnahan et al, ) and free‐ranging polar bears, including those in this study, rarely exceed this speed (Pagano, Carnahan et al, ; Whiteman et al, ). Another factor that can influence the relationship between ODBA and V̇O 2 , and thus cost of locomotion, is uneven surfaces including moving on rough or icy surfaces, and traversing inclines and declines (Halsey, ; Halsey et al, ).…”
Section: Discussionmentioning
confidence: 57%
“…Energy expenditure during nonswimming behaviors was based on the relationship between ODBA and oxygen consumption (V̇O 2 ) derived by Pagano, Carnahan et al (). However, Pagano, Carnahan et al () found a negative intercept between ODBA and V̇O 2 and suggested this relationship needed to be further developed. This negative intercept may have been related to head movements of the bears during resting V̇O 2 and ODBA measurements.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations